Taking up space - Gerber, Alyson (Scholastic Press, 2021)
Twelve-year old Sarah is used to being the star on her basketball team, playing with her best friends, but suddenly she finds that her body is changing and she does not understand why she cannot keep up on the court, plus she does not understand why her mother has gotten so weird about food, binging on candy while forgetting about dinner, and she really does not understand why she told Benny, her crush, about her mother--but when Benny offers to teach her how to cook and suggests she partners with him in a cooking competition she starts to find a way to stand up for herself and change her life for the better.